Synthesis and Characterization of Sodium Silicate Produced from Corncobs as a Heterogeneous Catalyst in Biodiesel Production - Alwi Gery Agustan Siregar; Renita Manurung; Taslim Taslim (Universitas Gadjah Mada, 2021)
In this study, silica derived from corncobs impregnated with sodium hydroxide to obtain sodium silicate was calcined, prepared, and employed as a solid base catalyst for the conversion of oils to biodiesel. The catalyst was characterized by X-Ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope Energy Dispersive X-Ray Spectroscopy (SEM-EDS), and Brunauer-Emmet-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods. Gas Chromatography-Mass Spectrometry (GC-MS) was used to characterize the biodiesel products. The optimum catalyst conditions were calcination temperature of 400 °C for 2 h, catalyst loading of 2%, and methanol: oil molar ratio of 12:1 at 60 °C for 60 min, that resulted in a yield of 79.49%. The final product conforms to the selected biodiesel fuel properties of European standard (EN14214) specifications. Calcined corncob-derived sodium silicate showed high potential for use as a low-cost, high-performance, simple-to-prepare solid catalyst for biodiesel synthesis.